Profesionalisme, Komitmen Organisasi, Kepuasan Kerja terhadap Kinerja Karyawan PDAM Tirta Kencana Samarinda - Muliaty, Muliaty (Sam Ratulangi University, 2021)
This study aims to determine the effect of professionalism, organizational commitment, and job satisfaction on the employee performance of PDAM Tirta Kencana, Samarinda City. It is hoped that this research can help find solutions to improve employee performance and service to customers of PDAM Tirta Kencana, Samarinda City. The data analysis method used is path analysis using Partial Least Square (PLS). The research object is the employees of PDAM Tirta Kencana, Samarinda City with a sample size of 60 employees from a population of 150 employees. The results showed that professionalism did not have a significant effect on employee performance and organizational commitment, job satisfaction had an effect on employee performance. PDAM Tirta Kencana must strive to improve the quality of employees through education and training and continue to develop and construct raw water treatment facilities into clean water so that the distribution of clean water distribution from the PDAM to the community can be handled.